Motivating and Rewarding Health Workers: Impact on Patient Care Quality - saeed Hamad Saleh Al Yami; Mohammed Hamed Almahmoud; Abdulrahman Saleh Fadel Al-Aqeel; Nouf Fadel Muhammad Al-Aqeel; Saleh Hamad Hussain Al Zubayed; Hassan Mohmmad Al Mansoor; Mana Abdullah Saleh Al Abbas; Ali hasan al Jamhour; Ibrahim Hussain Hassan Majrashi; Maryam Ibrahim Mansour Qabour (International Journal of Medical Toxicology and Legal Medicine, 2024)
Motivating and Rewarding Health Workers: Impact on Patient Care Quality Providing people with adequate health care is a long-term investment, recognized by the beneficial effect that good health has on economic growth. Ensuring a harmonious and motivated health workforce is crucially important to health systems, as health workers are essential for every aspect of the care that patients need. Knowing the impact different models of financial and non-financial motivation may have on the performance of health workers and their allocation of effort and time is an essential factor, not just in addressing the typical problems that affect all firms’ staff but also in improving health care quality within and across countries, thereby enabling health systems to achieve better health outcomes. For developing countries, this issue is particularly relevant. A potential mismatch in maximizing social welfare is widely recognized in the health sector: governments are seen as having two principal roles: maximizing patient welfare and ensuring health workers’ satisfaction by guaranteeing that they are adequately motivated in their role and have the necessary working conditions.